Transgender peoples' experiences and perspectives about general healthcare: A systematic review. Issue 4 (2nd October 2018) - Heng, Audrey; Heal, Clare; Banks, Jennifer; Preston, Robyn
Abstract: Background: Healthcare plays a vital role in the health and quality of life of transgender people, particularly those who wish to medically and/or surgically transition. In these cases, healthcare experiences can have a significant impact on the transgender person's perception of healthcare and future interactions with the healthcare system. Aim: To explore and systematically review the literature related to transgender peoples' experiences and perspectives of general healthcare. Methods: A systematic search of MEDLINE, CINAHL, Scopus, Web of Science, Informit, and PsycINFO was performed according to established search strategies. Results were screened for eligibility in two parts. Titles and abstracts were screened for relevance, and then full-texts were retrieved and screened using eligibility criteria, resulting in 20 articles of primary research included in the review. Data were extracted from the studies and thematically analyzed to synthesize findings. Results: Four main themes were identified relating to healthcare provider (HCP) knowledge, HCP communication, relationship dynamics, and healthcare systems. These reflected a subtheme of perceived underlying cisnormativity and transphobia which influenced transgender patients' interactions with the healthcare system. Participants also provided suggestions for improved care experiences. Discussion: Findings from prior studies and reviews about other transgender healthcare related topics describe similar themes and recommendations from participants. This reflects an impetus towards shared dialog and compromise between HCPs, policy makers and transgender patients to listen to each other's experiences and work collaboratively to improve transgender healthcare. Further research is necessary to explore and target geographic, demographic, and specific healthcare aspects regarding potential implementation of these recommendations.